Night falls on Manhattan [videorecording (DVD)] - Lumet, Sidney, 1924-2011; Garcia, Andy; Dreyfuss, Richard; Olin, Lena; Gandolfini, James; Daley, Robert, 1930- (Paramount ; Distributed by Warner Home Video, 2006)
Sean Casey is just another idealistic assistant D.A. until his prosecution of a cop-killing drug lord catapults him into the center of New York's tempestuous political arena. Vowing to follow the clues wherever they lead, the young D.A. embarks on a search for the truth that will force him to question his faith in the law, his loyalty to loved ones, and his place in a system where justice is the ultimate con.